Determinación del comportamiento de consumo horario residencial de agua potable en el Cantón Guaranda - Rea Chela, Johan Alexander (2024)
The Guaranda canton, belonging to the province of Bolívar in Ecuador, is located in the country's south-central part and is characterized by seven drinking water distribution networks. These networks are identified as the Chaquishca network, the La Humberdina network, the Primero de Mayo network, the Juan XXI network, the Los Lirios network, the Los Tanques network, and the Fausto Bazantes network. The main focus of this research work is the determination of residential hourly consumption of drinking water and its behavior concerning socioeconomic strata, from Class A to Class D, according to the classification proposed by (Arellano et al., 2018). . . The methodology used includes collecting data in the field, with particular attention to the reading of 175 micrometers distributed in the different networks 24 hours a day, seven days a week. As the research progresses, the conditions and behavior patterns of users about the consumption of drinking water are identified. It is possible to establish the variation curves of hourly consumption, highlighting the peaks of consumption and the coefficients of variation of hourly consumption (kh) in both their maximum and minimum values. It is determined that the Chaquishca network has a maximum consumption at 12h00 of 48.37 l/h, the Primero de Mayo network a maximum consumption at 7h00 of 136.95 l/h, the Juan XXI network a maximum consumption at 7h00 of 123.95 l/h. h. h, maximum consumption of the Los Lirios network at 12:00 p.m. of 111.05 l/h, the Los Tanques network a maximum consumption at 8:00 a.m. of 122.95 l/h, and the Fausto Bazantes network a maximum consumption at 7:00 p.m. of 122.85 l/h. It is relevant to mention that some of the values of the coefficients of variation of hourly consumption (kh) exceed the limit of 2.30, suggested by the CPE INEN standard (1992). The kh in the Chaquishca network stands out 2.33 and 2.44, in the La Humberdina network 2.61, in the Los Tanques network 2.92 and in the Maldonado network 2.96 and 2.99.